Variation in Leishmania chemokine suppression driven by diversification of the GP63 virulence factor. - Alejandro L Antonia; Alyson B Barnes; Amelia T Martin; Liuyang Wang; Dennis C Ko (Public Library of Science (PLoS), 2021)
Leishmaniasis is a neglected tropical disease with diverse outcomes ranging from self-healing lesions, to progressive non-healing lesions, to metastatic spread and destruction of mucous membranes. Although resolution of cutaneous leishmaniasis is a classic example of type-1 immunity leading to self-healing lesions, an excess of type-1 related inflammation can contribute to immunopathology and metastatic spread. Leishmania genetic diversity can contribute to variation in polarization and robustness of the immune response through differences in both pathogen sensing by the host and immune evasion by the parasite. In this study, we observed a difference in parasite chemokine suppression between the Leishmania (L.) subgenus and the Viannia (V.) subgenus, which is associated with severe immune-mediated pathology such as mucocutaneous leishmaniasis. While Leishmania (L.) subgenus parasites utilize the virulence factor and metalloprotease glycoprotein-63 (gp63) to suppress the type-1 associated host chemokine CXCL10, L. (V.) panamensis did not suppress CXCL10. To understand the molecular basis for the inter-species variation in chemokine suppression, we used in silico modeling to identify a putative CXCL10-binding site on GP63. The putative CXCL10 binding site is in a region of gp63 under significant positive selection, and it varies from the L. major wild-type sequence in all gp63 alleles identified in the L. (V.) panamensis reference genome. Mutating wild-type L. (L.) major gp63 to the L. (V.) panamensis sequence at the putative binding site impaired cleavage of CXCL10 but not a non-specific protease substrate. Notably, Viannia clinical isolates confirmed that L. (V.) panamensis primarily encodes non-CXCL10-cleaving gp63 alleles. In contrast, L. (V.) braziliensis has an intermediate level of activity, consistent with this species having more equal proportions of both alleles. Our results demonstrate how parasite genetic diversity can contribute to variation in immune responses to Leishmania spp. infection that may play critical roles in the outcome of infection.